Healthcare providers’ experiences in delivering the pictorial and text-based personalised asthma action plan - Cheong, Ai Theng; Shariff Ghazali, Sazlina; Salim, Hani; Lee, Ping Yein; Mohamad, Fadzilah; Lim, Poh Ying; Hussein, Norita; Hanafi, Nik Sherina; Ramdzan, Siti Nurkamilla; Ramli, Rizawati; Tam, Siow Foon; Nordin, Norasnita; et al. (International Primary Care Respiratory Group, 2025)
Introduction Asthma self-management improves clinical outcomes. We developed and implemented in primary care practice a pictorial personalised asthma action plan (pictorial-PAAP) to facilitate supported asthma self-management and aimed to compare its effectiveness with text-based PAAP (text-PAAP). This paper presents the healthcare providers’ (HCPs) experience and perception regarding the use of both pictorial- and text-based asthma action plans during patient counselling.